Analysis of Suspension Bridge with different Types of Anchoring Considering Vehicular Loading using SAP2000 - Jyotiprakash Sahu; Radeep Ku. Nirmal; Okesh Singh (International Journal of Scientific Research in Civil Engineering, 2022)
Cable-stayed and suspension bridges are two types of cable-supported bridges. One of the most common styles of long-span bridges, suspension bridges offer a number of advantages in terms of the stiffening girders’ height-span ratio and material qualities. The main cables of a suspension bridge are held in place by the anchorages, which are also made up of main beams, tower piers, cables, and anchorages. Based on the main cable anchoring method, suspension bridges are classified into self-anchored or earth-anchored. In a self-anchored bridge type, the main cable is directly attached to the stiffening girder, whereas in the earth-anchored type, the main cable is directly attached to the bridge via anchorages at the beginning and end locations.